Abrasive wear analysis of RZ5/TiC in-situ composites: a statistical approach. Issue 9 (26th September 2019) - Mehra, Deepak; Mahapatra, Manas Mohan; Harsha, Suraj Prakash
Abstract : Purpose: The RZ5 mg alloy is used in automotive and aerospace applications including helicopter gearboxes and aircraft components. These components are prone to the wear as per the demands. The present work is the study of the significance of hard particle/ceramic, i.e. titanium carbide (TiC) in RZ5 mg alloy to protect the machine components from wear. Design/methodology/approach: The abrasive wear analysis of in-situ RZ5-TiC magnesium matrix composite is considered for the study. The primary focus of the present work is to analyze the effects of varying control parameters, i.e. Wt.% of TiC, sliding distance and applied load on the responses, i.e. weight loss and coefficient of friction. Full factorial design of the experiment based on statistical analysis is used. Findings: It is observed that the individually Wt.% of TiC and sliding distance show the comparatively significant effect on both responses. Similarly, the interaction between sliding distance and Wt.% of TiC indicated the considerable impact on weight loss. The regression equations are developed and validated for estimating responses. It is observed that the percentage errors are not appearing more than 10 per cent of responses. Therefore, the close agreement between measured and predicted values shows the adequacy of the model. The control factor is optimized using multi-response optimization. The variations of the order of 2.47 and 2.35 per cent in target value of the coefficient of friction and weight loss are achieved. Originality/value: The current manuscript provides a detailed abrasive wear statistical analysis of RZ5-TiC composite. The influence of control parameters on the responses using the full factorial design, the main effect plots and interaction effects are presented.